Species Concepts as Applied to the Whitefly Bemisia tabaci Systematics：How Many Species Are There - LIU, Shu-sheng; Colvin, John; De Barro, Paul J (Journal of Integrative Agriculture, 2012)
The worldwide distribution and extensive genetic diversity of the whitefly,Bemisia tabaci,has long been recognized.However,the levels of separation within B.tabaci and the nomenclature of the various genetic groups have been a subject of debate.Recent phylogenetic analyses indicate that B.tabaci is a complex composed of 28 morphologically indistinguishable species.In this article,we first review the debate and difficulties associated with B.tabaci＇s taxonomy and systematics,and argue for the need to apply the biological species concept in order to elucidate B.tabaci＇s systematics.We summarize the accumulated genetic and behavioural data on reproductive incompatibilities evident amongst phylogenetic mtCOI groups of B.tabaci.Crossing studies have been conducted with 14 of the 28 putative species covering 54 reciprocal inter-species pairs,and observations on mating behaviour have been conducted for seven species pairs.Data from both crossing trials and behavioural observations indicate a consistent pattern of reproductive isolation among the putative species.We then discuss the technical and conceptual complexities associated with crossing experiments and behavioural observations designed to reveal reproductive incompatibility.Finally,we elaborate on a strategy for further clarifying the pattern of reproductive isolation between B.tabaci groups and propose future research directions on the systematics of this complex.